Material for rapidly consolidating quicksand surface and use method thereof
By using a mixed material of bentonite and metallurgical slag, the bonding and cementitivity of the hydration reaction are used to solve the problem of difficulty in consolidation of the quicksand surface, and the rapid consolidation of quicksand and the reduction of sandstorms are achieved, which has significant environmental protection and economic benefits.
Patent Information
- Application Number
- CN202311362715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to quickly and effectively consolidate the quicksand surface, resulting in frequent occurrence of environmental disasters such as sandstorms.
Bentonite and metallurgical slag are used as raw materials, and through a specific proportion of mixing and hydration reaction, a material with adhesiveness and cementation is formed, sprayed or poured on the surface of quicksand to achieve rapid consolidation.
It realizes rapid consolidation of the surface of quicksand, forming a hard plate-like block, reducing the movement of quicksand and the occurrence of dust storms, and has the advantages of rich raw materials, simple construction, low cost, and long-lasting and stable.
Smart Images

Figure CN119859044A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of quicksand management, and in particular to a material for rapidly consolidating the surface of quicksand and a method for using the material. Background Art
[0002] Desertification is the most important environmental and socio-economic problem plaguing the world today.
[0003] Quicksand refers to the mobile sand dunes or sand flows formed after the sand is blown by the wind or washed by water. It is characterized by being loose and moving at a fast speed, which can easily lead to land degradation and ecological environment damage. Quicksand is a common geomorphic phenomenon in arid desert areas. Since the soil is often very loose, it is easily affected by wind and water erosion, which leads to land erosion and the formation of various forms of quicksand. In particular, the mobile sand dunes, due to their huge volume, large exposed area, and fine sand particles, are easily blown by the wind, causing changes in the morphology of the land surface, destroying vegetation, destroying the habitats of animals and plants, affecting biodiversity and ecological balance, and further aggravating the process of desertification. In winter and spring, quicksand is also prone to form major natural disasters such as sandstorms, which have a destructive impact on human health and the ecosystem. Therefore, quicksand is obviously harmful to humans, buildings, farmland, water resources and ecosystems.
[0004] Fixing and controlling quicksand in arid areas is a complex problem, because quicksand is a very mobile loose sediment, and fixing it requires some special techniques and methods. It is crucial to seek scientific measures and methods to control and prevent quicksand according to local conditions. In the past few decades, many methods for controlling quicksand have been developed and put into practice. Common methods for controlling quicksand in arid areas include:
[0005] Vegetation coverage: Planting plants suitable for local environmental conditions in arid areas, such as Artemisia ordosica, Salix psammophila, and Tamarix chinensis, can help fix quicksand and maintain soil. The roots of plants can penetrate into quicksand and form a stable soil structure, thereby reducing the fluidity of quicksand, increasing the soil's resistance to wind erosion and water retention, and slowing down the formation and movement of quicksand.
[0006] Construction of shelterbelts: Build shelterbelts in areas prone to quicksand. By planting trees, shrubs or herbaceous plants with strong adaptability, a natural barrier will be formed to reduce the impact of wind on sand and prevent the spread of quicksand.
[0007] Geotechnical sand fixation technology: The use of geotechnical materials and technologies can help fix quicksand. Geotechnical sand fixation projects include the construction of artificial structures such as geotextiles, geogrids, sand nets, sand barriers, and sand walls. Through artificial means, conditions are created to resist wind erosion, increase soil stability, and slow down the development and migration of quicksand. In addition, geotechnical fillers can be used to fill quicksand areas to increase soil density, stability, and wind erosion resistance.
[0008] Binders and hardeners: Use special chemicals such as starch, cement, asphalt, etc. to bind sand particles together to form a stable structure and help fix the quicksand.
[0009] Soil and water conservation measures: Take appropriate soil and water conservation measures, such as building ditches and drainage systems, to reduce the harmful accumulation of surface runoff and prevent water from eroding the soil, thereby slowing down the formation of quicksand.
[0010] However, the above methods must be based on the specific geographical environment and governance objectives, comprehensively consider soil conditions, climate characteristics, water resources and other factors, and adopt a combination of multiple means to achieve the control and prevention of quicksand. Therefore, it is urgent to develop a simple, effective, low-cost and environmentally friendly material and method to consolidate quicksand. Summary of the invention
[0011] The purpose of this application is to provide a material for quickly consolidating the surface of quicksand and a method of using the material to quickly consolidate the loose surface of quicksand and reduce the movement of quicksand, thereby effectively reducing the occurrence of environmental disasters such as sandstorms. The specific technical solution is as follows:
[0012] The first aspect of the present application provides a material for consolidating the surface of quicksand, the raw material components including a consolidating agent and water, the consolidating agent being selected from at least one of bentonite and metallurgical slag; wherein the mass ratio of the bentonite to water is (0.1-30):100, preferably (1-15):100; the mass ratio of the metallurgical slag to water is (0.1-45):100, preferably (5-25):100.
[0013] In one embodiment of the present application, the mass ratio of the bentonite, the metallurgical slag and the water is (0.1-30):(0.1-45):100.
[0014] In one embodiment of the present application, the mass ratio of the bentonite, the metallurgical slag and the water is (1-15):(5-25):100.
[0015] In one embodiment of the present application, the D90 particle size of the bentonite is 20-150 μm, preferably 38-75 μm; preferably, the loose bulk density of the bentonite is 0.8-1.4 g / cm 3; Preferably, the moisture content of the bentonite is 10%-16%.
[0016] In one embodiment of the present application, the D90 particle size of the metallurgical slag is 25-100 μm, preferably 30-45 μm; preferably, the loose bulk density of the metallurgical slag is 1.2-1.5 g / cm 3 ; Preferably, the moisture content of the metallurgical slag is 7%-10%.
[0017] In one embodiment of the present application, the bentonite is selected from at least one of sodium-based bentonite and non-sodium-based bentonite.
[0018] In one embodiment of the present application, the metallurgical slag is selected from at least one of electric furnace slag, open-hearth furnace slag, converter slag and blast furnace slag.
[0019] In one embodiment of the present application, the raw material components further include a mineral gelling agent; preferably, the mass ratio of the mineral gelling agent to the water is (0.1-30):100, preferably (1-5):100.
[0020] In one embodiment of the present application, the mineral gelling agent is selected from at least one of fly ash, lime powder, cement, cement kiln dust, gypsum powder and phosphogypsum powder.
[0021] The second aspect of the present application provides the use of the material for consolidating the surface of quicksand according to the first aspect of the present application in consolidating the surface of quicksand.
[0022] The third aspect of the present application provides a method for using the material for consolidating the surface of quicksand described in the first aspect of the present application, comprising: mixing all raw material components, stirring evenly to obtain a mixed slurry; applying the mixed slurry to the surface of the quicksand; wherein the application method is selected from: spraying on the surface of the quicksand, pouring on the surface of the quicksand in a grid form, or mixing with the quicksand on the surface and then pressing into a mud cake and applying it to the surface of the quicksand.
[0023] In one embodiment of the present application, in the method for using the material for consolidating the surface of quicksand, when the raw material component includes metallurgical slag, it also includes: spraying water mist on the surface of the quicksand within 3-7 days after applying the mixed slurry to the surface of the quicksand; preferably, the time interval between the spraying is 1-2 days.
[0024] In one embodiment of the present application, the penetration depth of the mixed slurry into the surface of the quicksand is 2-10 mm.
[0025] In one embodiment of the present application, the spraying method is selected from pressure spraying or non-pressure spraying.
[0026] In one embodiment of the present application, the spraying device is selected from at least one of a sprayer, a watering can, a high-pressure spray gun, an agricultural sprinkler, a sprinkler truck, an aircraft spray device and an aircraft-carried spray device.
[0027] Beneficial effects of this application:
[0028] The present application provides a material for rapidly consolidating the surface of quicksand and a method for using the material. By using industrial solid waste such as metallurgical slag as raw materials, waste is turned into treasure and environmental pressure is reduced. By using bentonite or metallurgical slag alone, or by using bentonite and metallurgical slag in combination in a specific ratio, since bentonite and metallurgical slag have hydration reaction characteristics and adhesion, the sand particles on the surface of the quicksand can be cemented and agglomerated to form a whole, so that the surface of the quicksand can be rapidly consolidated and petrified into a hard block in the form of a plate, and can be stable for a long time in the natural environment, thereby achieving the purpose of consolidating the surface of the quicksand and reducing the movement of the quicksand. The application has the advantages of abundant raw materials, simple construction, low cost, and long-term stability. The quicksand can be rapidly consolidated and the occurrence of environmental disasters such as sandstorms can be effectively reduced. The application has broad application prospects and high practical value.
[0029] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0031] Figure 1 It is a diagram showing the effects of the experimental group and the control group in Example 1; in the figure: 1-experimental group, 2-control group. DETAILED DESCRIPTION
[0032] The technical solution of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0033] In a first aspect, the present application provides a material for consolidating the surface of quicksand, wherein the raw material components include a consolidating agent and water, wherein the consolidating agent is selected from at least one of bentonite and metallurgical slag; wherein the mass ratio of the bentonite to water is (0.1-30):100, preferably (1-15):100; the mass ratio of the metallurgical slag to water is (0.1-45):100, preferably (5-25):100.
[0034] In some embodiments of the present application, the mass ratio of the bentonite, the metallurgical slag and the water is (0.1-30): (0.1-45): 100, preferably (1-15): (5-25): 100. In some embodiments of the present application, for 100 parts by weight of water, the mass of the bentonite can be 0.1 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 30 parts by weight, or any two of the above values as endpoints. The mass of metallurgical slag can be 0.1 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 23 parts by weight, 25 parts by weight, 28 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or any two of the above values as endpoints. The present application controls the mass ratio of bentonite and water, metallurgical slag and water within the above range, which can better play the effect of consolidating the loose quicksand surface. The effect of bentonite and metallurgical slag consolidating quicksand may vary due to changes in factors such as the mass ratio of bentonite and metallurgical slag, water content and application method.
[0035] In some embodiments of the present application, the bentonite is selected from at least one of sodium bentonite and non-sodium bentonite. Bentonite is a clay with montmorillonite as the main mineral component. Montmorillonite is an aluminum silicate mineral with a layered structure. The silicate layers are separated by hydrated exchangeable cations (such as Ca 2+ 、Na + Mg 2+ , Fe 2+ , H + Due to the blade-like crystal structure of montmorillonite and the imbalance of electric charges within the crystal layer, bentonite has a high specific surface area, ion exchange, adsorption and unique water absorption and expansion characteristics. When bentonite is mixed with water, it can form a sticky colloid that binds and agglomerates loose sand particles and forms hardened lumps after drying. It can exist stably for a long time in a dry environment and can help stabilize loose quicksand and reduce quicksand migration. In addition to montmorillonite, bentonite usually contains a small amount of impurity minerals such as quartz, feldspar, mica, zeolite, and illite.
[0036] The main chemical components of bentonite include SiO 2 (58wt%-70wt%) and Al 2 O 3 (15wt%-20wt%), also including Fe 2 O 3 (2wt%-3.5wt%), MgO (2wt%-6wt%), CaO (0.2wt%-4.5wt%), Na 2 O (0.1wt%-3.5wt%), TiO 2 (0.1wt%-0.5wt%), etc. According to the main types and amount of exchangeable cations between the layers of the montmorillonite crystal structure, bentonite is usually divided into sodium montmorillonite, calcium bentonite, hydrogen bentonite (such as activated clay, natural bleaching earth-acidic clay), lithium bentonite, organic bentonite and other types. The content of montmorillonite in sodium bentonite is usually 40wt%-90wt%; among them, the exchangeable Na + The total amount of cations is greater than 50%. Non-sodium bentonite includes calcium bentonite, hydrogen bentonite (such as activated clay, natural bleaching earth-acidic clay), organic bentonite, etc.
[0037] In some embodiments of the present application, the metallurgical slag is selected from at least one of electric furnace slag, open-hearth steel slag, converter steel slag and blast furnace slag. Metallurgical slag includes steel slag and blast furnace slag. Steel slag is waste slag produced in the steelmaking process, including three categories: electric furnace slag, open-hearth steel slag and converter steel slag. The cooling treatment process of steel slag includes cold abandonment method, pan water cooling method, hot pouring method, water quenching method, wind quenching method, hot stuffing method, drum method and pressurized steam aging method. Steel slag is a bulk industrial solid waste, and its generation rate is 12%-15% of crude steel output. In 2021, the national steel slag production exceeded 120 million tons, and the social accumulated steel slag has reached more than 800 million tons, and the accumulated amount is increasing at an annual rate of 80 million tons. my country produces a large amount of steel slag, but the comprehensive utilization rate of resources is low, which has a serious impact on the environment. The main chemical components of steel slag include: CaO (40wt%-60wt%), Fe 2 O 3 (15wt%-30wt%), SiO 2 (10wt%-35wt%), MgO (0.5wt%-5wt%), Al 2 O 3 (3wt%-12wt%), MnO (0.5wt%-5wt%) and a small amount of sulfide; the main mineral components include dicalcium silicate (C 2 S), tricalcium silicate (C 3S), oxide phase (solid solution of FeO, MgO, MnO) and a small amount of free calcium oxide (f-CaO). Since steel slag contains free CaO and free MgO, has large fluctuations in composition and performance, expands when exposed to water, has low gelling activity, and has poor volume stability, it is difficult to control its quality in construction projects such as cement, concrete, and roads. Therefore, it is generally considered to be a difficult-to-use industrial solid waste, resulting in a low comprehensive utilization rate. However, these shortcomings do not affect the consolidation of steel slag on the surface of quicksand. The presence of free calcium oxide and magnesium oxide also helps to strengthen the synergistic cementation of steel slag and bentonite.
[0038] Steel slag powder is a fine powder obtained by crushing and processing steel slag. It has strong volcanic ash activity, silicate chemical reaction ability and cementing property. After mixing with water, the phase components such as calcium silicate, active calcium oxide and active magnesium oxide contained in the steel slag powder will undergo hydration reaction. The reaction products such as hydrated calcium silicate and calcium hydroxide can quickly form a colloidal film on the surface of loose sand particles, so that the sand particles can be bonded to each other. After coagulation and hardening, a petrified hard crust is formed on the surface of the quicksand. Therefore, after the steel slag powder is mixed with water and sprayed on the surface of the quicksand, the fluid sand particles can be consolidated through hydration reaction, so that the surface of the quicksand can be stabilized.
[0039] Blast furnace slag is a porous, amorphous silicate molten byproduct produced during the blast furnace ironmaking process. Its main chemical components include CaO, MgO, SiO 2 and Al 2 O 3 The main mineral components include pyroxene, dicalcium silicate, pseudowollastonite, pyroxene and plagioclase. Blast furnace slag has good chemical activity. After mixing with water, the dicalcium silicate and other components it contains can generate hydrated calcium silicate, etc., which cement the sand particles and gradually harden them. According to statistics from the China Iron and Steel Association, China's annual production of blast furnace slag reached 170 million tons in 2020. The treatment methods of blast furnace slag include water quenching and dry granulation.
[0040] The applicant believes that: bentonite will swell when absorbing water, and it is easy to peel montmorillonite into thin flakes; it forms a colloid after hydration and is easy to disperse; it has lubricity; it has the ability to adsorb and bond other particles; the water contained in bentonite evaporates more slowly than other materials; and it has plasticity. When used to consolidate quicksand, bentonite has a unique property, that is, when the bentonite slurry is mixed with dry quicksand or soil, the bentonite, which originally dries slowly, can use the capillary action of the quicksand or soil to quickly discharge the water it contains, so that the sand and soil are quickly consolidated and hardened. Metallurgical slag is rich in highly active calcium silicate, which can produce cementing properties after hydration reaction. Metallurgical slag is crushed, ground, etc. to obtain metallurgical slag powder. After metallurgical slag powder is mixed with bentonite, the bonding properties of the two materials can work synergistically: the alkaline characteristics of metallurgical slag can promote the dispersion of bentonite, and the water absorption of bentonite can promote the hydration process of calcium silicate, calcium ferrite and active calcium oxide in the metallurgical slag powder. The hydration reaction of metallurgical slag powder helps to improve the consolidation strength of bentonite.
[0041] The raw water used in this application can be tap water or other water sources (such as rainwater, river water, pond water, seawater, etc.).
[0042] In some embodiments of the present application, the D90 particle size of the bentonite is 20-150 μm, preferably 38-75 μm. The D90 described in the present application refers to the particle size at which the cumulative distribution of particles is 90%, that is, the mass content of particles smaller than this particle size accounts for 90% of the total mass of all particles. The present application controls the D90 particle size of the bentonite within the above range, which can not only save the crushing and grinding cost of the bentonite, but also enable it to work better with metallurgical slag powder, thereby exerting the effect of consolidating the surface of the quicksand.
[0043] In some embodiments of the present application, the loose bulk density of the bentonite is 0.8-1.4 g / cm 3 The present application controls the loose bulk density of bentonite within the above range, which can not only save the crushing and grinding cost of bentonite, but also enable it to work better with metallurgical slag powder, thereby exerting the effect of consolidating the surface of quicksand.
[0044] In some embodiments of the present application, the water content of the bentonite is 10%-16%. The water content described in the present application refers to the ratio of the mass of each type of water molecules in the bentonite after drying to the total mass of the bentonite. The present application controls the water content of the bentonite within the above range, so that it can better cooperate with the metallurgical slag powder, thereby exerting the effect of consolidating the surface of the quicksand.
[0045] In some embodiments of the present application, the D90 particle size of the metallurgical slag is 25-100 μm, preferably 30-45 μm. The D90 described in the present application refers to the particle size at which the cumulative distribution of particles is 90%, that is, the mass content of particles smaller than this particle size accounts for 90% of the total mass of all particles. The present application controls the D90 particle size of the metallurgical slag within the above range, which can not only save the cost of crushing and grinding the metallurgical slag, but also enable it to work better with bentonite, thereby exerting the effect of consolidating the surface of the quicksand.
[0046] In some embodiments of the present application, the loose bulk density of the metallurgical slag is 1.2-1.5 g / cm 3 The present application controls the loose bulk density of the metallurgical slag within the above range, which can not only save the cost of crushing and grinding the metallurgical slag, but also enable it to work better with bentonite, thereby exerting the effect of consolidating the surface of the quicksand.
[0047] In some embodiments of the present application, the water content of the metallurgical slag is 7%-10%. The water content described in the present application refers to the ratio of the mass of free water in the metallurgical slag to the mass of the metallurgical slag after drying. The present application controls the water content of the metallurgical slag within the above range, so that it can better cooperate with bentonite, thereby exerting the effect of consolidating the surface of the quicksand.
[0048] In some embodiments of the present application, the raw material components further include a mineral gelling agent. The present application can enhance the effect of consolidating the surface of the quicksand by using the mineral gelling agent.
[0049] In some embodiments of the present application, the mass ratio of the mineral gelling agent to the water is (0.1-30):100, preferably (1-5):100. In some embodiments of the present application, for 100 parts by weight of water, the mass of the mineral gelling agent can be 0.1 parts by weight, 1 parts by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 23 parts by weight, 25 parts by weight, 28 parts by weight, 30 parts by weight, or a value within the range formed by any two of the above values as endpoints. The present application controls the mass ratio of the mineral gelling agent to water to (0.1-30):100, so that it can better cooperate with bentonite and metallurgical slag, thereby exerting the effect of consolidating the quicksand; the present application controls the mass ratio of the mineral gelling agent to water to (1-5):100, so that it can better cooperate with bentonite and metallurgical slag, thereby better exerting the effect of consolidating the surface of the quicksand; and better save costs.
[0050] In some embodiments of the present application, the mineral gelling agent is selected from at least one of fly ash, lime powder, cement, cement kiln dust, gypsum powder and phosphogypsum powder. The hydraulic cementing materials such as fly ash, lime powder, cement, cement kiln dust, gypsum powder and phosphogypsum powder used in the present application are helpful to strengthen the hardening of bentonite and the consolidation effect on sand.
[0051] The second aspect of the present application provides the application of the material for consolidating the surface of quicksand described in the first aspect of the present application in consolidating the surface of quicksand. The material for consolidating the surface of quicksand described in the first aspect of the present application is applicable to terrain surfaces of any shape, and there is no restriction on the terrain of the quicksand surface. The material for consolidating the surface of quicksand described in the first aspect of the present application can also be used for other loose powders or material piles such as coal yards, construction earthworks, mineral powder piles, etc., as well as the consolidation or strengthening treatment of soil surfaces.
[0052] The third aspect of the present application provides a method for using a material for consolidating the surface of quicksand, comprising: (1) mixing all raw material components and stirring them evenly to obtain a mixed slurry; (2) applying the mixed slurry to the surface of the quicksand; wherein the application method is selected from: spraying on the surface of the quicksand, pouring on the surface of the quicksand in a grid form, or mixing with the quicksand on the surface and then pressing it into a mud cake and applying it to the surface of the quicksand.
[0053] In step (1) of the present application, all the raw material components are mixed. All the raw material components can be mixed in one step or in steps. For example, it can specifically include the steps of: mixing bentonite and water in proportion, stirring and fully dispersing the bentonite in the water to obtain a viscous bentonite suspension; adding metallurgical slag in proportion to the bentonite suspension, and continuing to stir to form a soil-slag mixed suspension slurry; and adding a mineral gelling agent to the soil-slag mixed suspension slurry as needed, stirring evenly, to obtain a mixed slurry.
[0054] The present application has no particular restriction on the stirring method, for example, mechanical stirring or manual stirring can be used; the equipment used for the mechanical stirring method can be selected from a blade stirrer, a magnetic stirrer, an air flow stirrer, a hydraulic circulation stirrer, a drum stirrer, etc.
[0055] The preparation process of the mixed slurry described in this application can be carried out at the site to be sprayed, and the mixed slurry should be applied within 6 hours after preparation, and the best effect is achieved within 2 hours. The specific application method and steps may vary according to different requirements, quicksand surface conditions, and raw material components used.
[0056] The application method of the present application is selected from spraying the mixed slurry on the surface of quicksand. If the mixed slurry is too viscous, a small amount of water can be added to adjust the viscosity of the mixed slurry until the spraying is smooth and the mixed slurry does not block the nozzle outlet of the spraying device; if precipitation occurs during spraying, the mixed slurry should be stirred and kept in a suspended state.
[0057] The present application is to pour the material on the surface of the quicksand in a grid form, and then first lay out the grid on the quicksand, and then pour the material directly on the surface of the quicksand in a grid form to form a petrified grid. The pouring grid can be continuous or discontinuous.
[0058] The present application method is selected from the following steps: mixing with the quicksand on the surface, pressing into a mud cake and applying it on the quicksand surface. The mixed slurry can be first stirred with the quicksand, then pressed into a mud cake and applied on the quicksand surface to form a petrified grid.
[0059] The method described in this application can also be used in conjunction with other methods of consolidating quicksand, such as geotechnical sand fixation and vegetation coverage, to enhance the effect of consolidating the quicksand surface; when applied, the mixed slurry described in this application can be directly sprayed over the geogrid or planted plants. The mixed slurry is safe for plants.
[0060] The present application applies the mixed slurry to the surface of quicksand. Since bentonite, metallurgical slag and mineral gelling agent have hydration reaction characteristics and adhesion, the sand particles on the surface of the quicksand can be cemented and agglomerated into a whole, thereby consolidating and petrifying the surface of the quicksand into plate-like hard blocks, and maintaining long-term stability in the natural environment, thereby achieving the purpose of consolidating the surface of the quicksand and reducing the movement of the quicksand. The application has the advantages of abundant raw materials, simple construction, low cost, and long-term stability. It can effectively utilize industrial solid waste and reduce the occurrence of environmental disasters such as sandstorms.
[0061] In some embodiments of the present application, when the raw material component includes metallurgical slag, the process further includes: spraying water mist on the surface of the quicksand within 3-7 days after applying the mixed slurry containing metallurgical slag powder to the surface of the quicksand; preferably, the spraying interval is 1-2 days. The present application sprays water mist on the surface of the quicksand to keep the newly solidified surface of the quicksand moist, which can make the hydration reaction of the metallurgical slag powder more complete and achieve a better consolidation effect. After the present application applies the mixed slurry to the surface of the quicksand, it is best to avoid heavy mechanical loads and water scouring to ensure the consolidation effect.
[0062] In some embodiments of the present application, the spray water mist is selected from at least one of a sprayer, a watering can, a high-pressure spray gun, an agricultural sprinkler device, a sprinkler truck, an aircraft (including a drone) spray device, and an aircraft-carried spray device.
[0063] In some embodiments of the present application, the penetration (wetting) depth of the mixed slurry on the quicksand surface is 2-10 mm. The present application controls the penetration (wetting) depth of the mixed slurry on the quicksand surface within the above range, which can better consolidate the quicksand surface and save costs.
[0064] In some embodiments of the present application, the spraying method is selected from pressure spraying or pressure-free spraying. Pressure spraying refers to placing the slurry mixture to be sprayed in a spray container, sealing it, and pressurizing it, and then causing the mixed slurry to be sprayed out from the nozzle of the spray device through the pressure in the container. Pressure-free spraying refers to the mixed slurry being sprinkled from the nozzle of the spray device onto the surface of the sand body to be sprayed under normal pressure by its own gravity. When spraying, the present application is preferably sprayed in the windward direction of the quicksand surface; the spraying pressure and spraying speed can be adjusted during spraying so that the mixed slurry is evenly dispersed and covered on the quicksand surface.
[0065] In some embodiments of the present application, the spraying device is selected from at least one of a sprayer, a watering can, a high-pressure spray gun, an agricultural sprinkler, a sprinkler truck, an aircraft (including a drone) spray device, and an aircraft-carried spray device.
[0066] The present application adopts industrial solid waste such as metallurgical slag as raw materials, turning waste into treasure and reducing environmental pressure; by using bentonite or metallurgical slag alone, or using bentonite and metallurgical slag in a specific proportion, since both bentonite and metallurgical slag have hydration reaction characteristics and adhesion, the sand particles on the surface of the quicksand can be cemented and agglomerated into a whole, so that the surface of the quicksand can be quickly consolidated and petrified into hard blocks in the form of plates, and can be stable for a long time in the natural environment, so as to achieve the purpose of consolidating the surface of the quicksand and reducing the movement of the quicksand. It has the advantages of abundant raw materials, simple construction, low cost, and long-term stability. It can quickly consolidate the surface of the quicksand and can effectively reduce the occurrence of environmental disasters such as sandstorms; it has broad application prospects and high practical value.
[0067] <Bearable weight test method>
[0068] On the surface of the quicksand that has been consolidated (experimental group), a representative test position is randomly selected, and an iron sheet with a length and width of 2 cm and a thickness of 3 mm is horizontally placed on it; a metal weight is loaded on the iron sheet, and the changes in the consolidated surface are observed at the same time; the weight is continued to be loaded until the consolidated surface breaks or collapses; when cracks or depressions begin to appear on the consolidated surface, the total weight (g) of the load loaded on the consolidated surface is recorded and recorded as the total tolerable weight. The total tolerable weight is divided by the area of the iron sheet (4 cm 2 ) to obtain the pressure that the test position can withstand. Select 5 representative positions on each construction sample for testing to obtain the average (arithmetic mean) weight and pressure that the sample can withstand (unit: Pa, N / m 2).
[0069] As a comparative sample, the dry sand surface without consolidation treatment (control group) was also tested for its compressive strength in the same way, and the total weight when the load began to sink was taken as the total weight that could be supported.
[0070] Example
[0071] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0072] Example 1
[0073] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and flattened with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand body in the typical desert quicksand of Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region, with a D90 particle size of 350 μm), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0074] The bentonite clay ore produced by Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 75 μm, that is, 90 wt% was less than 75 μm (200 mesh), and the loose bulk density was 1.3 g / cm 3 , water content is 12%, expansion capacity ≥ 10mL / g, and blue absorption capacity is 32% (ie 32g / 100g).
[0075] The converter steelmaking slag (hot smoldering slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, the magnetic particles were removed by a magnet, and then ground by a ball mill to make converter slag powder. The D90 particle size of the converter slag powder was 45 μm, that is, 90 wt% was less than 45 μm (325 mesh), and the loose bulk density was 1.5 g / cm 3 , the moisture content is 10%.
[0076] At the test site to be constructed, 10 kg of bentonite powder was placed in a mixer, and 150 kg of tap water was added to the mixer. The mixture was stirred to fully disperse the bentonite in the water to prepare a bentonite suspension with adhesiveness; 15 kg of converter slag powder was added to the bentonite suspension, and stirring was continued to form a soil-slag mixed suspension slurry; 3 kg of No. 325 cement was added to the soil-slag mixed suspension slurry, and stirring was continued to uniformly disperse the mixture to obtain a mixed slurry.
[0077] After the mixed slurry is prepared, the mixed slurry is divided into two equal parts, and one of the parts is randomly selected and sprayed evenly on the surface of the pre-laid loose quicksand block (experimental group) through a sprayer, so that it is evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reaches 3-5mm. During the spraying process, a stirring rod is used to stir the slurry in the sprayer to keep the particles in the sprayer in a suspended state.
[0078] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the sand after construction to keep the surface of the sand moist and avoid heavy mechanical loads and water scouring.
[0079] One month after the construction (mixed slurry applied to the sand surface), the average pressure that the consolidated surface can withstand before deformation is 62566Pa (Pa, N / m 2 ); while the untreated natural sand is still in a loose state, and the average pressure it can withstand before deformation is 2941Pa.
[0080] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2 ), there will be thunderstorms and heavy rains on 6 days. Figure 1 As shown in the figure, after the impact of the above-mentioned weather changes, the consolidation layer on the surface of the sand body treated by consolidation (1-experimental group) remained intact, but the sand body surface of the untreated control block (2-control group) was severely eroded by wind and rain. It can also be seen that some loose sand bodies under the consolidation cover layer were eroded by rainwater to form cavities at the edge of the consolidation block, but the consolidation layer remained intact.
[0081] After the mixed slurry constructed on the surface of the loose sand body dries, due to the adhesiveness and chemical reaction bonding effect of the mixed slurry of bentonite, steel slag powder and mineral adhesive, the sand particles on the surface of the loose flowable sand body are cemented and agglomerated to form plate-like blocks, covering the surface of the loose flowable sand body, thereby effectively preventing wind erosion on the surface of the sand body.
[0082] Example 2
[0083] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and leveled with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand in the typical desert quicksand of Wengniute, Chifeng City, Inner Mongolia Autonomous Region), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0084] The bentonite clay ore of Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 75 μm, that is, 90 wt% was less than 75 μm (200 mesh), and the loose bulk density was 1.3 g / cm 3 , water content is 12%, expansion capacity ≥10mL / g, and blue absorption is 32%.
[0085] The converter steelmaking slag (hot smoldering slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, the magnetic particles were removed by a magnet, and then ground by a ball mill to make converter slag powder. The D90 particle size of the converter slag powder was 30 μm, that is, 90 wt% was less than 30 μm (500 mesh), and the loose bulk density was 1.4 g / cm 3 , the moisture content is 10%.
[0086] At the construction site, 5 kg of bentonite powder is placed in a mixer, and 150 kg of tap water is added to the mixer, and the mixture is stirred to fully disperse the bentonite in the water to prepare a bentonite suspension with adhesiveness; 20 kg of converter slag powder is added to the bentonite suspension, and stirring is continued to form a soil-slag mixed suspension slurry; 2 kg of lime powder is added to the soil-slag mixed suspension slurry, and stirring is continued to uniformly disperse the mixture to obtain a mixed slurry.
[0087] After the preparation of the mixed slurry, the slurry was immediately divided into two parts. One hour later, one part was randomly selected from the mixed slurry and sprayed evenly on the surface of the pre-laid quicksand block (experimental group) through a sprayer, so that it was evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reached 3-5mm. During the spraying process, a stirring rod was used to stir the slurry in the sprayer to keep the particles in a suspended state.
[0088] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the sand after construction to keep the surface of the sand moist and avoid heavy mechanical loads and water scouring.
[0089] After the construction is completed (one month after the mixed slurry is applied to the sand surface, the average pressure that the consolidated surface can withstand before deformation is 65214Pa according to the weight test per unit area; while the untreated natural sand is still in a loose state, and the average pressure that it can withstand before deformation is 3005Pa.
[0090] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2 ), and there were thunderstorms and rainstorms for 6 days. After the impact of the above weather changes, the consolidation layer on the surface of the sand body that has been consolidated remained intact, but the sand body surface of the untreated control block was severely eroded by wind and rain. It can also be seen that some loose sand bodies under the consolidated cover layer at the edge of the consolidated block were eroded by rain to form cavities, but the consolidation layer remained intact.
[0091] After the mixed slurry constructed on the surface of the loose sand body dries, due to the adhesiveness and chemical reaction bonding effect of the mixed slurry of bentonite, steel slag powder and mineral adhesive, the sand particles on the surface of the loose flowable sand body are cemented and agglomerated to form plate-like blocks, covering the surface of the loose flowable sand body, thereby effectively preventing wind erosion on the surface of the sand body.
[0092] Example 3
[0093] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and leveled with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand in the typical desert quicksand in Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0094] The bentonite clay ore of Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 75 μm, that is, 90 wt% was less than 75 μm (200 mesh), and the loose bulk density was 1.3 g / cm 3, water content is 12%, expansion capacity ≥10mL / g, and blue absorption is 32%.
[0095] The blast furnace slag (water quenched slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, naturally air-dried, and then ground with a ball mill to make blast furnace slag powder. The D90 particle size of the blast furnace slag powder was 45 μm, that is, 90 wt% was less than 45 μm (325 mesh), and the loose bulk density was 1.5 g / cm 3 , the moisture content is 9%.
[0096] At the construction site, 10 kg of bentonite powder is placed in a mixer, and 150 kg of tap water is added to the mixer. The mixture is stirred to fully disperse the bentonite in the water to prepare a bentonite suspension with adhesive properties. 12 kg of blast furnace slag powder is added to the bentonite suspension, and stirring is continued to form a soil-slag mixed suspension slurry. Stirring is continued to uniformly disperse the mixture to obtain a mixed slurry.
[0097] After the mixed slurry is prepared, the slurry is divided into two equal parts. One hour later, one of the parts is randomly selected and sprayed evenly on the surface of the pre-laid loose quicksand block (experimental group) through a sprayer, so that it is evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reaches about 5-10mm. During the spraying process, a stirring rod is used to stir the slurry in the sprayer to keep the particles in a suspended state.
[0098] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the sand block after construction to keep the sand surface moist and avoid heavy mechanical loads and water scouring.
[0099] One month after the construction was completed (mixed slurry was applied to the sand surface), the weight-bearing test per unit area showed that the average pressure that the consolidated surface could withstand before deformation was 57859Pa; while the untreated natural sand was still in a loose state, and the average pressure that it could withstand before deformation was 3123Pa.
[0100] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2), and there were thunderstorms and rainstorms for 6 days. After the impact of the above weather changes, the consolidation layer on the surface of the sand body that has been consolidated remained intact, but the sand body surface of the untreated control block was severely eroded by wind and rain. It can also be seen that some loose sand bodies under the consolidated cover layer at the edge of the consolidated block were eroded by rain to form cavities, but the consolidation layer remained intact.
[0101] After the mixed slurry constructed on the surface of the loose sand body dries, due to the adhesiveness and chemical reaction cementation of the mixed slurry of bentonite and steel slag powder, the sand particles on the surface of the loose flowable sand body are cemented and agglomerated to form plate-like blocks, covering the surface of the loose flowable sand body, thereby effectively preventing wind erosion on the surface of the sand body.
[0102] Example 4
[0103] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and leveled with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand in the typical desert quicksand in Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0104] The bentonite clay ore of Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 38 μm, that is, 90 wt% was less than 38 μm (400 mesh), and the loose bulk density was 1.2 g / cm 3 , water content is 11%, expansion capacity ≥10mL / g, and blue absorption is 32%.
[0105] The blast furnace slag (water quenched slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, naturally air-dried, and then ground with a ball mill to make blast furnace slag powder. The D90 particle size of the blast furnace slag powder was 45 μm, that is, 90 wt% was less than 45 μm (325 mesh), and the loose bulk density was 1.5 g / cm 3 , the moisture content is 9%.
[0106] The converter steelmaking slag (hot-splashed slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, the magnetic particles were removed by a magnet, and the converter slag powder was ground by a ball mill. The D90 particle size of the converter slag powder was 30 μm, that is, 90 wt% was less than 30 μm (500 mesh), and the loose bulk density was 1.4 g / cm 3 , the moisture content is 10%.
[0107] At the construction site, 8 kg of bentonite powder is placed in a mixer, and 150 kg of tap water is added to the mixer. The mixture is stirred to fully disperse the bentonite in the water to prepare a bentonite suspension with adhesive properties. 7 kg of blast furnace slag powder is added to the bentonite suspension, followed by 10 kg of converter steel slag powder. The mixture is stirred continuously to form a soil-slag mixed suspension slurry. The mixture is stirred continuously to uniformly disperse the mixture to obtain a mixed slurry.
[0108] After the mixed slurry is prepared, the mixed slurry is divided into two equal parts, and one of the parts is sprayed evenly on the surface of the pre-laid quicksand block (experimental group) through a sprayer, so that it is evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reaches about 5 mm. During the spraying process, a stirring rod is used to stir the slurry in the sprayer to keep the particles in the sprayer in a suspended state.
[0109] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the sand after construction to keep the surface of the sand moist and avoid heavy mechanical loads and water scouring.
[0110] One month after the construction was completed (mixed slurry was applied to the sand surface), the weight-bearing test per unit area showed that the average pressure that the consolidated surface could withstand before deformation was 57075Pa; while the untreated natural sand was still in a loose state, and the average pressure that it could withstand before deformation was 3087Pa.
[0111] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2 ), and there were thunderstorms and rainstorms for 6 days. After the impact of the above weather changes, the consolidation layer on the surface of the sand body treated by consolidation remained original without obvious damage, but the surface of the sand body in the untreated control block was severely eroded by wind and rain. It can also be seen that some loose sand bodies under the consolidation cover layer were eroded by rain to form cavities at the edge of the consolidation block, but the consolidation layer remained intact.
[0112] After the mixed slurry on the surface of the sand body dries, due to the adhesiveness and chemical reaction bonding effect of the mixed slurry of bentonite, steel slag powder and mineral adhesive, the sand particles on the surface of the loose and flowable sand body are cemented and agglomerated to form plate-like blocks, covering the surface of the loose and flowable sand body, thereby effectively preventing wind erosion on the surface of the sand body.
[0113] Example 5
[0114] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and flattened with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand body in the typical desert quicksand of Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region, with a D90 particle size of 350 μm), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0115] The converter steelmaking slag (hot smoldering slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, the magnetic particles were removed by a magnet, and then ground by a ball mill to make converter slag powder. The D90 particle size of the converter slag powder was 45 μm, that is, 90 wt% was less than 45 μm (325 mesh), and the loose bulk density was 1.5 g / cm 3 , the moisture content is 10%.
[0116] At the test site to be constructed, add 150kg of tap water and 25kg of converter slag powder into the mixer and stir to form a uniformly dispersed suspended slurry. Divide the above suspended slurry into two equal parts, and randomly select one of them, and spray it evenly on the surface of the pre-laid loose quicksand block (experimental group) through a sprayer, so that it is evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reaches 3-5mm. During the spraying process, use a stirring rod to stir the slurry in the sprayer to keep the particles in it in a suspended state.
[0117] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the sand after construction to keep the surface of the sand moist and avoid heavy mechanical loads and water scouring.
[0118] One month after the construction was completed (mixed slurry was applied to the sand surface), the weight-bearing test per unit area showed that the average pressure that the consolidated surface could withstand before deformation was 61547Pa; while the untreated natural sand was still in a loose state, and the average pressure that it could withstand before deformation was 3155Pa.
[0119] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2 ), and there were thunderstorms and rainstorms for 6 days. After the impact of the above weather changes, the consolidation layer on the surface of the sand body treated by consolidation (experimental group) remained intact, but the sand body surface of the untreated control block (control group) was severely eroded by wind and rain. It can also be seen that some loose sand bodies under the consolidation cover layer were eroded by rainwater to form cavities at the edge of the consolidation block, but the consolidation layer remained intact.
[0120] After the mixed slurry constructed on the surface of the loose sand body dries, due to the adhesion and chemical reaction characteristics of the steel slag powder slurry, the sand particles on the surface of the loose flowable sand body are cemented and agglomerated to form plate-like blocks, covering the surface of the loose flowable sand body, thereby effectively preventing rainwater scouring and wind erosion on the surface of the sand body.
[0121] Example 6
[0122] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and leveled with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand body in the typical desert quicksand of Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region, with a D90 particle size of 350 μm. The surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0123] The bentonite clay ore produced by Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 75 μm, that is, 90 wt% was less than 75 μm (200 mesh), and the loose bulk density was 1.3 g / cm 3 , water content is 12%, expansion capacity ≥10mL / g, and blue absorption is 32%.
[0124] At the test site to be constructed, add 150kg of tap water and 18kg of bentonite powder into the mixer and stir thoroughly to form a uniformly dispersed suspended slurry. Divide the above suspended slurry into two equal parts, and randomly select one of them, and spray it evenly on the surface of the pre-laid loose quicksand block (experimental group) through a sprayer, so that it is evenly dispersed and covered on the surface of the sand body, and the penetration depth of the slurry reaches 3-5mm. During the spraying process, use a stirring rod to stir the slurry in the sprayer to keep the particles in it in a suspended state.
[0125] One month after the construction was completed (slurry was applied to the sand surface), the weight-bearing test per unit area showed that the average pressure that the consolidated surface could withstand before deformation was 56416Pa; while the untreated natural sand was still in a loose state, and the average pressure that it could withstand before deformation was 3046Pa.
[0126] After the construction was completed (the mixed slurry was applied to the surface of the sand), the sand with the surface consolidation treatment (experimental group) and the control sand without consolidation treatment (control group) continued to be exposed to the open field and left for continuous comparative observation for more than one month. During this period, according to the official records of the National Meteorological Administration, the field site experienced continuous high temperatures of 30-35℃ and wind exposure, and there were 2 days with wind speeds exceeding level 4 (wind speed 5.5-10.7m / s, wind pressure 18.9-71.6N / m 2 ), and there were 7 days with wind force reaching level 3 (wind speed 3.4-5.4m / s, wind pressure 7.2-18.2N / m 2 ), and there were thunderstorms and rainstorms for 6 days. After the impact of the above weather changes, the consolidation layer of the sand surface treated by consolidation (experimental group) was damaged by rainstorms in some parts, and the rest of the surface remained intact. However, the sand surface of the untreated comparison block (control group) was severely eroded by wind and rain.
[0127] After the slurry applied on the surface of the loose sand body dries, due to the adhesion and adsorption of the bentonite slurry, the sand particles on the surface of the loose sand body are cemented and agglomerated to form plate-like blocks, which cover the surface of the loose and flowable sand body, thereby effectively preventing rainwater scouring and wind erosion on the surface of the sand body.
[0128] Example 7
[0129] The hard soil surface with an inclination angle of 2-2.5 degrees was weeded and flattened with a bulldozer to make the surface smooth and keep the inclination. Two blocks of loose quicksand layers with a thickness of 50 mm and an area of 4 m×4 m were laid on the hard soil surface (one block was used for consolidation treatment (experimental group) and the other block was used for comparative observation (control group); the quicksand was taken from the fine sand body in the typical desert quicksand of Wengniute Banner, Chifeng City, Inner Mongolia Autonomous Region, with a D90 particle size of 350 μm), and the surface of the sand layer was scraped flat to keep the thickness uniform and parallel to the hard soil surface below.
[0130] The bentonite clay ore of Qingjian Mining Co., Ltd. in Chaoyang City, Liaoning Province was crushed and dried, and then ground with a ball mill to make bentonite powder (model QJCa-01). The D90 particle size of the bentonite powder was 75 μm, that is, 90 wt% was less than 75 μm (200 mesh), and the loose bulk density was 1.3 g / cm 3 , water content is 12%, expansion capacity ≥10mL / g, and blue absorption is 32%.
[0131] The converter steelmaking slag (hot smoldering slag) produced by Liaoning Lingyuan Iron and Steel Co., Ltd. was crushed to less than 0.5 cm, the magnetic particles were removed by a magnet, and then ground by a ball mill to make converter slag powder. The D90 particle size of the converter slag powder was 45 μm, that is, 90 wt% was less than 45 μm (325 mesh), and the loose bulk density was 1.5 g / cm 3 , the moisture content is 10%.
[0132] At the quicksand site to be constructed, 10 kg of bentonite powder is placed in a mixer, 150 kg of tap water is added to the mixer, and the mixture is stirred to fully disperse the bentonite in the water to prepare a bentonite suspension with adhesiveness; 15 kg of converter slag powder is added to the bentonite suspension, and stirring is continued to form a soil-slag mixed suspension slurry; 3 kg of No. 325 cement is added to the soil-slag mixed suspension slurry, and stirring is continued to uniformly disperse the mixture to obtain a mixed slurry.
[0133] After the mixed slurry is prepared, it is divided into two equal parts, one of which is randomly selected, and the mixed slurry is poured on the surface of the quicksand in a 1m×1m grid using a funnel, and the penetration depth of the mixed slurry reaches about 10mm. During the pouring process, a stirring rod is used to stir the slurry to keep the particles in it suspended.
[0134] On the 3rd and 5th day after the spraying is completed, use a sprayer to spray water mist on the surface of the consolidation grid after construction to keep the consolidation surface moist and avoid heavy mechanical loads and water scouring.
[0135] After drying, a grid-like petrified sand barrier is formed on the sand surface.
[0136] Embodiment 8-11
[0137] Except for adjusting the raw material ratio as shown in Table 1, the rest is the same as Example 1.
[0138] Comparative Examples 1-3
[0139] Except for adjusting the raw material ratio as shown in Table 1, the rest is the same as Example 1.
[0140] Table 1 Parameters of Examples 1, 8-11, and Comparative Examples 1-3
[0141]
[0142]
[0143] From the above results, it can be seen that the types of bentonite, metallurgical slag, and mineral gelling agent in Examples 1-11, and the mass ratio of bentonite, metallurgical slag, mineral gelling agent and water are controlled within the scope of this application. One month after the construction is completed (the slurry is applied to the surface of the sand body), the unit area can withstand weight test. The average value of the pressure that the consolidated surface can withstand before deformation is 56416Pa and above, and it remains in its original appearance for one month without damage; while the untreated natural sand body is still loose, and the average value of the pressure that can be withstood before deformation is about 3000Pa. Without being limited to any theory, the inventor of this application believes that: because bentonite and metallurgical slag have hydration reaction characteristics and adhesion, they can make the sand particles on the surface of the quicksand cement and agglomerate to form a whole, so that the surface of the loose quicksand is quickly consolidated and petrified into a hard block in the form of a plate, so as to achieve the purpose of consolidating the quicksand surface and reducing the movement of the quicksand; in addition, the mineral gelling agent can also enhance the effect of consolidating the quicksand surface.
[0144] The amount of mineral gelling agent in Comparative Example 1 was not controlled within the scope of the present application, and the amounts of bentonite and metallurgical slag used were relatively low, resulting in a weight-bearing test per unit area one month after the completion of the construction (slurry was applied to the surface of the sand body). The average value of the pressure that the consolidated surface could withstand before deformation was 6374 Pa, the surface of the quicksand was weakly consolidated, and the quicksand was destroyed or washed away by rain in many places.
[0145] The amount of bentonite used in Comparative Example 2 was not controlled within the scope of this application, and the amounts of metallurgical slag and mineral adhesives used were relatively low, resulting in a weight-bearing test per unit area one month after the construction was completed (slurry was applied to the surface of the sand body). The average value of the pressure that the consolidated surface could withstand before deformation was 6025 Pa, the surface of the quicksand was weakly consolidated, and the quicksand was destroyed or washed away by rain in many places.
[0146] The amount of metallurgical slag in Comparative Example 3 was not controlled within the scope of this application, and the amounts of bentonite and mineral adhesives used were relatively low, resulting in a weight-bearing test per unit area one month after the construction was completed (slurry was applied to the surface of the sand body). The average value of the pressure that the consolidated surface could withstand before deformation was 5394 Pa, the surface of the quicksand was weakly consolidated, and the quicksand was destroyed or washed away by rain in many places.
[0147] The present application provides a material for rapidly consolidating the surface of quicksand and a method for using the material. By using industrial solid waste such as metallurgical slag as raw materials, waste is turned into treasure and environmental pressure is reduced. By using bentonite or metallurgical slag alone, or by using bentonite and metallurgical slag in a specific proportion, since bentonite and metallurgical slag have adhesive properties, the sand particles on the surface of the quicksand can be cemented and agglomerated to form a whole, so that the surface of the quicksand can be rapidly consolidated and petrified into a hard block in the form of a plate, and can be stable for a long time in the natural environment, thereby achieving the purpose of consolidating the surface of the quicksand and reducing the movement of the quicksand. The application has the advantages of abundant raw materials, simple construction, low cost, and long-term stability. The quicksand can be rapidly consolidated and the occurrence of environmental disasters such as sandstorms can be effectively reduced. The application has broad application prospects and high practical value.
[0148] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A material for consolidating the surface of quicksand, characterized in that: The raw material components include a consolidating agent and water, wherein the consolidating agent is selected from at least one of bentonite and metallurgical slag; wherein, The mass ratio of bentonite to water is (0.1-30):100, preferably (1-15):100; The mass ratio of the metallurgical slag to water is (0.1-45):100, preferably (5-25):
100.
2. The material for consolidating the surface of quicksand according to claim 1, characterized in that: The mass ratio of the bentonite, the metallurgical slag and the water is (1-15):(5-25):
100.
3. The material for consolidating the surface of quicksand according to claim 1 or 2, characterized in that: The D90 particle size of the bentonite is 20-150 μm, preferably 38-75 μm; preferably, the loose bulk density of the bentonite is 0.8-1.4 g / cm 3 ; Preferably, the moisture content of the bentonite is 10%-16%; The D90 particle size of the metallurgical slag is 25-100 μm, preferably 30-45 μm; preferably, the loose bulk density of the metallurgical slag is 1.2-1.5 g / cm 3 ; Preferably, the moisture content of the metallurgical slag is 7%-10%.
4. The material for consolidating the surface of quicksand according to claim 1 or 2, characterized in that: The bentonite is selected from at least one of sodium-based bentonite and non-sodium-based bentonite; Preferably, the metallurgical slag is selected from at least one of electric furnace slag, open-hearth furnace slag, converter slag and blast furnace slag.
5. The material for consolidating the surface of quicksand according to claim 1 or 2, characterized in that: The raw material components also include a mineral gelling agent; preferably, the mass ratio of the mineral gelling agent to the water is (0.1-30):100, preferably (1-5):
100.
6. The material for consolidating the surface of quicksand according to claim 5, characterized in that: The mineral gelling agent is selected from at least one of fly ash, lime powder, cement, cement kiln dust, gypsum powder and phosphogypsum powder.
7. Use of the material for consolidating quicksand surface according to any one of claims 1 to 6 in consolidating quicksand surface.
8. A method for using the material for consolidating the surface of quicksand according to any one of claims 1 to 6, characterized in that: include: Mix all raw material components and stir evenly to obtain a mixed slurry; The mixed slurry is applied to the surface of the quicksand; wherein the application method is selected from: spraying on the surface of the quicksand, pouring on the surface of the quicksand in a grid form, or mixing with the quicksand on the surface and then pressing into a mud cake and applying it on the surface of the quicksand.
9. The method of use according to claim 8, characterized in that: When the raw material components include metallurgical slag, the method further includes: spraying water mist on the surface of the quicksand within 3-7 days after applying the mixed slurry to the surface of the quicksand; preferably, the spraying time interval is 1-2 days.
10. The method of use according to claim 8, characterized in that: The penetration depth of the mixed slurry on the surface of the quicksand is 2-10 mm; Preferably, the spraying method is selected from pressure spraying or pressure-free spraying; Preferably, the spraying device is selected from at least one of a sprayer, a watering can, a high-pressure spray gun, an agricultural sprinkler, a sprinkler truck, an aircraft spray device and an aircraft-carried spray device.